STRATEGI BADAN PENDAPATAN DAERAH KABUPATEN BUTON TENGAH DALAM UPAYA PENINGKATAN PENDAPATAN DAERAH - Samiun; Muh. Amir; Dwi Putranto Riau (Halu Oleo University, 2024)
This study aims to analyze the Regional Revenue Agency (BAPENDA) planning strategies of Buton Tengah Regency in increasing regional income. Using a qualitative approach, the study involved 20 respondents selected through a PSS (5:1) mechanism and 5 informants chosen purposively. Data collection was conducted through a series of in-depth interviews to evaluate organizational performance based on five key dimensions: productive efficiency, service standards, responsiveness, compliance level, and management transparency. Data analysis employed the interactive approach developed by Milles and Huberman. The findings indicate that the performance of BAPENDA Buton Tengah is rated as